Da'wah and Transformative Leadership: Tuan Imam's Role in Nurturing Islamic Values in Kampung Kasih Sayang - Jamaludin, Jamaludin; Junaidi, Junaidi; Nurainun, Nurainun; Pratama, Muhammad Yoga; Harahap, Nurul Febriyani (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
Originating from the nickname "Kampung Kasih Sayang," the Assembly of Fardu Ain Taklim is a village that harmonizes togetherness and equality in the values ​​of Islam and the Pancasila ideology. The esteemed Tuwan Imam leads this Village. Therefore, the research aims to understand the leadership qualities of Tuwan Imam in preserving the existence of Kampung Kasih Sayang. The research method employed is qualitative with a phenomenological approach. Data collection techniques involve participatory observation, in-depth interviews, and documentary studies. Data analysis follows Miles and Huberman's approach, encompassing data reduction, display, and verification. The ATLAS assists the entire analytical process software (Archive of Technology, Life-World, and Everyday Language). The research findings reveal that Tuwan Imam's leadership journey exemplifies sacrifice, love for the nation, religion, and moral values. Tuwan Imam provides nine requirements for joining the Village, along with five obligations and five prohibitions to be adhered to while living in Kampung Kasih Sayang. Tuwan Imam also implements three social concepts, including social structure, functional integrity, and social groups, fostering a communal life based on togetherness, equality, and mutual support. This gives rise to the principles of patience, gratitude, and sharing in Kampung Kasih Sayang. Tuwan Imam leadership reflects the principles of "Ing Ngarsa Sang Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani".